Coping With Human-Cat Interactions Beyond the Limits of Domesticity: Moral Pluralism in the Management of Cats and Wildlife - Wandesforde-Smith, Geoffrey; Levy, Julie K.; Lynn, William; Rand, Jacquie; Riley, Sophie; Schaffner, Joan E.; Wolf, Peter Joseph (Frontiers in Veterinary Science, 2021)
Although human interactions with cats are often even typically analyzed in the context of domesticity, with a focus on what sorts of interactions might make both people and cats "happy at home," a large number of cats in the world live, for one reason or another, beyond the bounds of domesticity. Human interactions with these more or less free-living cats raise deeply controversial questions about how both the cats and the people they interact with should be sensibly managed, and about the moral imperatives that ought to guide the management of their interactions through the laws and public policies regulating both human interactions with pets and with wildlife. We review the geography of human interactions with cats living beyond the bounds of domesticity. We acknowledge the contributions made to ideas about how to manage cats by the animal protection movement. We review the tensions that have emerged over time between advocates for the eradication of free-living cats, because of the impacts they have on native wildlife species, and those who have imagined alternatives to eradication, most notably one or another variant of trap-neuter-return (TNR). The conflict over how best to deal with cats living beyond the bounds of domesticity and their wildlife impacts raises the prospect of stalemate, and we canvass and critique possibilities for moving beyond that stalemate.